Perspective transformation among female reentry students at an evangelical Christian university - Wade, Debra H., author; Safarik, Lynn, advisor; Macleod, Meri J., committee member; Banning, James H., committee member; Morgan, George A., committee member (Colorado State University. Libraries, 2004)
The unique context of this study on transformative learning is framed by the evangelical Christian worldview. Within the context of the evangelical perspective there are highly conservative, traditional proponents of the Christian worldview who hold very specific, often thought of as limiting, ideas of the role of women in society and their ability to function as counterparts to men in the workplace. This study engages a dialogue about the processes of transformation in reentry women who embrace a Christian worldview and choose an evangelical Christian academic setting to complete an undergraduate degree. The process of transformation was understood through the storied lives of ten female undergraduate students between the ages of 35 and 63 who returned to college after an interruption in their post-secondary education of over five years and experiencing marital and family roles. A three interview process was employed to explore their lives as children and the messages they received as females; their experiences in the evangelical university classroom with other adult students; and their goals and plans for their futures after graduation. Their stories were analyzed to determine how the women assigned meaning to their lives given their evangelical Christian belief system, the traditional roles and identities they have assumed, and their goals after graduation. The interview protocol used open questioning to allow the women to narrate slices of their lives perceived as significant to the context of their enrollment at an evangelical Christian university. Field notes, an audio-taped journal, and communication with the committee chair triangulated interview data. Narrative analysis and a grounded theory approach were used in the analysis. A grounded theory of transformation for reentry women matriculating at an evangelical Christian university was developed based on the context of the women's past lives, present academic experiences, and the dialogic process articulated by the women as they told their stories. Findings regarding the process of transformation for these women were presented as a continuum occurring in four phases: (a) Conformity, (b) Self-denial, (c) Agency and (d) Empowerment. A model of transformation was developed demonstrating how the interplay of dialogic thinking, identity status/roles, and Christian worldview correlate to the four transformative phases.
Keywords: religious education; continuing education; women’s studies